Landslides and debrisflow processes of the Mangyshlak Peninsula - Lukashov, A.A. (НАО «Карагандинский национальный исследовательский университет имени академика Е.А. Букетова», 2025)
The zones of episodic, hydroclimatically triggered, high-mobility landslide and mudflow processes in Mangyshlak span multiple geomorphological settings. These include the Ustyurt Escarpment and adjacent isolated “island” plateaus, the foothill areas of the escarpment, peripheral zones of the peninsula’s lowmountain structures, coastal cliffs along the Caspian Sea, and the flanks of large depressions within the lowlying plateaus. The most prominent landslide complexes occur along the southeastern cliffs of the Karagiye Depression and the northern cliffs of the Tyub-Karagan Peninsula (particularly the massive Zhygylgan landslide complex). Primary mudflow activity is concentrated within the western valley systems of the Mangyshlak Peninsula and the northern valley networks draining into the Karagiye Depression. Orographically pronounced morphological complexes were predominantly formed during the Middle Pliocene, as evidenced by Akchagylian deposits abutting Mangyshlak’s coastal formations. The episodic occurrence of highly dynamic landslide and debris-flow processes spans several geomorphological settings across the Mangyshlak region [1, 2].
Маңғышлақ түбегінің көшкіндері мен селдері
Оползни и сели полуострова Мангышлак
Keywords: Landslides; debris flows; Mangyshlak; Tyub-Karagan; Karagiye Depression; Khvalynian marine terraces